Evaluation of Olfactory and Gustatory Functions in Patients With Fibromyalgia Syndrome: Its Relationship With Anxiety, Depression, and Alexithymia - Tuğba ÖZSOY-ÜNÜBOL,; Hakan KULLAKÇI,; İrem İLHAN,; Figen YILMAZ, (Archives of Rheumatology, 2020)
Objectives: This study aims to evaluate smell and taste functions in patients with fibromyalgia syndrome (FMS) and the relationship between smell and taste functions, anxiety, depression, alexithymia, and quality of life (QoL). Patients and methods: This cross-sectional study included 30 patients with FMS (3 males, 27 females; mean age 46.0±8.5 years; range, 18 to 70 years) and 20 age- and sex-matched healthy participants (2 males, 18 females; mean age 45.7±10.0 years; range, 18 to 70 years). Fibromyalgia Impact Questionnaire (FIQ) was applied to FMS patients. Hamilton Anxiety Scale, Depression Scale, Toronto Alexithymia Scale, and EuroQol Questionnaire Five-Dimensions (EQ-5D) were applied to all participants. Sniffin' Sticks test was used for olfactory function analysis while taste strips were used for gustatory function analysis. Results: The FMS patients had higher anxiety, depression, and alexithymia while lower QoL scores. Olfactory and gustatory function test scores were lower in FMS patients. Total olfactory function scores were 25.96 and 36.40 for FMS and control groups, respectively. For taste function, they were 9.93 and 13.55, respectively. These scores were negatively correlated with anxiety, depression, and alexithymia scores whereas positively correlated with EQ-5D index score. There was no significant correlation with FIQ score. Conclusion: Anxiety and depression are common symptoms of FMS. Patients with FMS had altered olfactory and gustatory functions and these impairments were correlated with their anxiety and depression. Further studies with larger sample sizes including functional magnetic resonance imaging evaluation should be performed.